Nondestructive quantitative method for evaluation of magnesium hydroxide on surface of coated fabrics from Raman spectra - Jiří Militký; Karel Kupka; Dana Křemenáková; Mohanapriya Venkataraman; Juming Yao; Guocheng Zhu (Scientific Reports)
Abstract Magnesium-based compounds, such as oxide (MgO) and hydroxide (Mg (OH)2), are used in various applications ranging from medicine to electrotechnics. Especially, magnesium hydroxide coatings of textile structures are frequently used as part of flame retardant compositions, antibacterial agents, and surface absorption of far infrared radiation. Numerous analytical techniques exist for evaluating these compounds on material surfaces. The main aim of this article is to propose a novel methodology for the non-destructive quantitative evaluation of Mg (OH)2 coatings on the surfaces of typical synthetic fibers in low concentrations by analyzing Raman spectra. A regression approach was used to determine the concentration of Mg (OH)2 based on the assumption of Raman spectra additivity of Mg (OH)2 and the synthetic fiber. A simple modification of the sensor for analyzing Raman spectra was implemented, ensuring accurate positioning along all three axes. This methodology was applied to the analysis of polyester and polyamide textiles with Mg (OH)2 coatings.